2013
DOI: 10.2169/internalmedicine.52.0570
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Autoimmune Syndrome Caused by an Adhesive Skin Patch Containing Loxoprofen-Sodium

Abstract: A 62-year-old woman complained of repeated hypoglycemic events. A 75g oral glucose tolerance test (75 gOGTT) showed a marked increase in the plasma insulin level and impaired glucose tolerance. The patient exhibited a high titer of plasma anti-insulin autoantibodies. Her diagnosis was insulin autoimmune syndrome (IAS). Following the cessation of loxoprofen-sodium (LOXs), she experienced no further hypoglycemic episodes. However, the hypoglycemic attacks recurred following the accidental readministration of LOX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…It has recently been demonstrated that albumin has a cysteine residue (Cys34) with a strong reducing capacity, like ALA. Kamei et al described a case of IAS occurring in a patient who was taking no drugs containing a sulfhydryl group, but who was taking albumin (29). Loxoprofen-sodium is capable of inducing IAS even when administered through adhesive skin patches (30). It is fundamentally important to obtain a patient's detailed clinical history in this context.…”
Section: Trigger Factors and Diseases Associated With Iasmentioning
confidence: 99%
“…It has recently been demonstrated that albumin has a cysteine residue (Cys34) with a strong reducing capacity, like ALA. Kamei et al described a case of IAS occurring in a patient who was taking no drugs containing a sulfhydryl group, but who was taking albumin (29). Loxoprofen-sodium is capable of inducing IAS even when administered through adhesive skin patches (30). It is fundamentally important to obtain a patient's detailed clinical history in this context.…”
Section: Trigger Factors and Diseases Associated With Iasmentioning
confidence: 99%
“…The SH group activates T-cells by cleaving the S-S bond of insulin to produce an antibody against insulin 6 , 7 ) . Additionally, loxoprofen without SH also reportedly causes IAS 8 ) . In IAS caused by drugs, hypoglycemia occurs 4–6 weeks after drug ingestion 9 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The plasma C-peptide levels in patients with IAS have also been indicated to be elevated, but it is much lower compared with the insulin concentration in the blood, showing a state of separation of C-peptide from insulin ( 8 ). IAA has a high titer; therefore, detection of IAA, serum insulin and C-peptide levels can assist with identification of this disorder ( 9 ).…”
Section: Discussionmentioning
confidence: 99%